Digital map of chemical fertility of soils of continental Ecuador - Martin López, Javier Mauricio; Jimenez, Wilmer; Calahorrano, Oscar; Caicedo Flaker, Juan D.; Silva, Mayesse Aparecida da (2023)
Digital tools are transforming and accelerating innovation in agriculture. Digital soil maps are important tools for better-informed decision-making supported by data and science. The maps permit addressing site-specific strategies needed by fertile and healthy soils to minimize the impacts of land use change, increase productivity without generating degradation and deforestation, and to deal with climate challenges.. To contribute to the diagnosis, monitoring, and control of soil degradation in Ecuador, the digital Map of Chemical Fertility of Soils of continental Ecuador and continuous soil properties maps of organic matter (%), pH (Un), available phosphorus (mg/kg), available potassium (cmol/kg), cation exchange capacity (cmol/kg), base sum (cmol/kg), base saturation (%), electrical conductivity (dS/m), clay (%) and sand (%) were developed by using digital soil mapping approaches, 13,552 soil profile data, and 46 environmental covariables.. The maps generated in this service are also available, the Geoportal of the Ministry of Agriculture and Livestock of Ecuador.